2022
DOI: 10.1186/s12877-022-03489-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and treatment patterns of older adults with dementia-related psychosis by dementia type in the United States

Abstract: Background Little is known about the incidence of clinical events and treatment patterns among older adults with dementia-related psychosis. Given that dementia-related psychosis comprises various dementia types, this study describes the incidence of clinical events and treatment patterns by dementia type after patients with dementia are diagnosed with psychosis. Methods Adults aged ≥ 65 years with dementia and newly diagnosed with psychosis were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Besides advanced age, there were many physical factors for increased risk of death; in this case the temporal relationship of the onset of delusion and the stroke could be a chance factor. However, it is also reported that dementia‐related psychosis 27 and very late onset psychosis 28,29 have higher mortality. The emergence of psychotic symptoms in patients with no such previous history may alert clinicians and caregivers to the possibility of impending deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides advanced age, there were many physical factors for increased risk of death; in this case the temporal relationship of the onset of delusion and the stroke could be a chance factor. However, it is also reported that dementia‐related psychosis 27 and very late onset psychosis 28,29 have higher mortality. The emergence of psychotic symptoms in patients with no such previous history may alert clinicians and caregivers to the possibility of impending deterioration.…”
Section: Discussionmentioning
confidence: 99%